Virological surveillance of human respiratory syncytial virus A and B at a tertiary hospital in Catalonia (Spain) during five consecutive seasons (2013–2018). (12th March 2019) - Gimferrer, Laura; Vila, Jorgina; Piñana, Maria; Andrés, Cristina; Rodrigo-Pendás, José A; Peremiquel-Trillas, Paula; Codina, María G; C Martín, María del; Esperalba, Juliana; Fuentes, Francisco; Rubio, Susana; Campins-Martí, Magda; et al.
Aim: Human respiratory syncytial virus (HRSV) is the main cause of respiratory tract infections among infants.Materials & methods: In the present study, the molecular epidemiology of HRSV detected from 2013 to 2017 has been described.Results: A 10% of collected samples were laboratory confirmed for HRSV. Patients under 2 years of age were the main susceptible population to respiratory syncytial virus disease, but an increasingly number of confirmed patients over 65 years of age was reported. Epidemics usually started in autumn and ended in spring. Both HRSV groups co-circulated every season, but the HRSV-B was the most predominant. HRSV-A and HRSV-B strains mainly belonged to ON1 and BA9 genotypes, respectively.Conclusion: The present study reports recent data about the genetic diversity of circulating HRSV in Spain.